PENDIDIKAN LITERASI FINANSIAL MELALUI PEMBELAJARAN FIQH MU'ĀMALĀT BERBASIS KITAB KUNING - Adib Rifqi Setiawan (Program Studi Pendidikan Islam, 2020)
This research goals to gain the design for a learning program to guide students in pondok pesantren on achieving financial literacy throughout fiqh mu'āmalāt learning that is based on kitab kuning. We used R&D approach 4D model that reduced into three stages: define, design, and develop. It was gained a syllabus that completed by lesson plan, student worksheets, nor assessment instrument as well, that validated by experts and practitioners and reliability counted based on test.